Glycogen Synthase Kinase 3β Modulates the Inflammatory Response Activated by Bacteria, Viruses, and Parasites - Cortés-Vieyra, Ricarda; Silva-García, Octavio; Gómez-García, Anel; Gutiérrez-Castellanos, Sergio; Álvarez-Aguilar, Cleto; Baizabal-Aguirre, Víctor M. (Frontiers in Immunology, 2021)
Knowledge of glycogen synthase kinase 3β (GSK3β) activity and the molecules identified that regulate its function in infections caused by pathogenic microorganisms is crucial to understanding how the intensity of the inflammatory response can be controlled in the course of infections. In recent years many reports have described small molecular weight synthetic and natural compounds, proteins, and interference RNA with the potential to regulate the GSK3β activity and reduce the deleterious effects of the inflammatory response. Our goal in this review is to summarize the most recent advances on the role of GSK3β in the inflammatory response caused by bacteria, bacterial virulence factors (i.e. LPS and others), viruses, and parasites and how the regulation of its activity, mainly its inhibition by different type of molecules, modulates the inflammation.